PENINGKATAN PENGETAHUAN TENTANG IVA TES UNTUK DETEKSI DINI KANKER LEHER RAHIM - Yuliaswati, Enny; Kamidah, K (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Background: Cervical cancer in Indonesia occupies the top position as a malignancy that causes death in women. Cervical cancer that infects women can actually be detected in various ways. One of them is through IVA examination. IVA examination is easy and inexpensive. But there are many obstacles that occur, so the majority of women are reluctant to do so. Embarrassed, feeling that there are no complaints and lack of knowledge dominates many women who are not willing to do an IVA examination. Objective: Community service is to increase knowledge about early detection of cervical cancer through IVA examination. Method: This activity was conducted one day in the form of an interactive discussion with material about early detection of cervical cancer. Based on observations during community service activities, several positive results were obtained, such as: 1). Participants consisting of 45 participants consisting of student guardians and teachers 2). The participants were active in the question and answer session. Results: Increased knowledge regarding methods of early detection of cervical cancer. The post-test results found 35 participants or 78% of participants answered correctly. The conclusion of this activity is education with interactive discussion can increase knowledge about how to detect early cervical cancer.   Background: Cervical cancer in Indonesia occupies the top position as a malignancy that causes death in women. Cervical cancer that infects women can actually be detected in various ways. One of them is through IVA examination. IVA examination is easy and inexpensive. But there are many obstacles that occur, so the majority of women are reluctant to do so. Embarrassed, feeling that there are no complaints and lack of knowledge dominates many women who are not willing to do an IVA examination. Objective: Community service is to increase knowledge about early detection of cervical cancer through IVA examination. Method: This activity was conducted one day in the form of an interactive discussion with material about early detection of cervical cancer. Based on observations during community service activities, several positive results were obtained, such as: 1). Participants consisting of 45 participants consisting of student guardians and teachers 2). The participants were active in the question and answer session. Results: Increased knowledge regarding methods of early detection of cervical cancer. The post-test results found 35 participants or 78% of participants answered correctly. The conclusion of this activity is education with interactive discussion can increase knowledge about how to detect early cervical cancer.